Resveratrol decreases extracellular traps (ETs) in acute promyelocytic leukemia (NB4) cells - Mahshid Vafajoo; Minoo Shahidi; Fahimeh Shahriyary; Mohammad Reza Amirzargar; Ahmad Kooshari (PLoS ONE, 2025)
Background Activated neutrophils can create structures known as neutrophil extracellular traps (NETs/ETs) consisting of nuclear components and granules. The ETOsis phenomenon leads to activating the platelets and coagulation factors. Accordingly, coagulation and fibrinolysis can be promoted. Resveratrol (RSV) is a botanical antioxidant with anti-inflammatory and anti-leukemia effects. The present study was conducted to assess the effect of RSV on the occurrence of ETOsis in the NB4 cell line. Methods Human acute promyelocytic leukemia cell line (NB4) were stimulated and treated by lipopolysaccharides (LPS) and RSV, respectively. Sytox green and a fluorescent microscope were used to assess the ETOsis in NB4 cells. Furthermore, the expression level of peptidylarginine deiminase 4 (PAD4) gene and the occurrence of ETOsis in NB4 cells were evaluated by real-time PCR and flow cytometry, respectively. Moreover, an enzyme-linked immunosorbent assay (ELISA) kit was utilized to measure tumor necrosis factor-α (TNF-α) cytokine. Results Following treatment with RSV, a significant decrease in PAD4 gene expression and TNF-α cytokine concentration in the supernatant of NB4 cell line culture medium was observed. Besides, the amount of ETOsis in the NB4 cells treated with LPS and RSV decreased. Conclusion The findings demonstrated that RSV can inhibit the process of ETOsis in NB4 cells. By inhibiting the process of ETOsis, RSV may be able to reduce the bleeding and, consequently, the failure after treatment in acute promyelocytic leukemia (APL) patients.